Topical Nepafenec in Eyes with Non-Central Diabetic Macular Edema - Friedman, Scott M. (Retina, 2015)
PURPOSE: To evaluate the effect of a topical non-steroidal anti-inflammatory drug, nepafenac 0.1%, in eyes with non-central diabetic macular edema (DME). METHODS: Multi-center double-masked randomized trial. Individuals with good visual acuity and non-center involved DME were randomly assigned to nepafenac 0.1% (N = 61) or placebo (nepafenac vehicle, N = 64) three times a day for 12 months. The primary outcome was mean change in OCT retinal volume at 12 months. RESULTS: Mean baseline retinal volume was 7.8 mm(3). At 12 months, in the nepafenac and placebo groups respectively, mean change in retinal volume was -0.03 mm(3) and -0.02 mm(3) (treatment group difference: -0.02, 95% CI: -0.27 to 0.23, P = 0.89). Central involved DME was present in 7 eyes (11%) and 9 eyes (14%) at the 12-month visit (P = 0.79), respectively. No differences in visual acuity outcomes were identified. One study participant developed a corneal melt after using nepafenac in the non-study eye, which had a history of severe dry eye. No additional safety concerns were evident. CONCLUSION: In eyes with non-central DME and good visual acuity, topical nepafenac 0.1% three times daily for 1 year likely does not have a meaningful effect on OCT-measured retinal thickness.